SCHOOL PRINCIPALS' STRATEGIES IN IMPROVING THE QUALITY OF EDUCATION - Amin, Ahmad Nur; Jazilurrahman, Jazilurrahman; Faqih, Moh. Mahfudz; Muali, Chusnul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Education is an important foundation in the development of a nation. Therefore, this research was conducted to describe the strategies implemented by the school principal in an effort to improve the quality of education at Taruna Dra Zulaeha Middle School, Leces. This research methodology uses a qualitative approach with descriptive methods, exploring data through in-depth interviews with school principals, teachers, as well as direct observation in the school environment, as well as documentation data. Data analysis was carried out through data reduction, data presentation and verification, with a focus on the strategies implemented by the school principal. Research findings show that school principals have implemented various holistic strategies. First, the school principal plans the program carefully, paying attention to the needs of educators and education staff, designing the curriculum, and establishing policies for adding subjects. Second, teacher development programs are an integral part of the strategy. Third, the school principal supervises the teaching and learning process, output and student development from the admissions process to graduation. In addition, the school principal is active in motivating and involving stakeholders, including parents and the community, to support improving the quality of education in schools. Through implementing this strategy, the quality of education at Taruna Dra Zulaeha Middle School, Leces, has experienced a significant increase. The research results show that the active participation of school principals in planning, implementing and evaluating educational policies has a positive impact on the quality of learning and student achievement.